SEROTYPING AND ANTIBIOGRAM OF E. COLI ISOLATES FROM ENDANGERED WILD CAPTIVE ANIMALS - Satpute, Ashlesha; Ingle, Sonal; Kalorey, D R; Sonegaonkar, Asmita; Zanzad, Suhasini; Nagdive, Anshuja; Katwate, S R (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
Seventeen fecal samples from wild captive animals were culturally screened. Seven were found to be positive for E.coli. These isolates were investigated for antibiogram, serotype and congo red binding assay. E.coli isolates belong to serotypes O17, O103, O147, O5, O52, O66 and rough type (1 each) indicating sharing of E.coli serotypes among wild life, domestic animals and human beings. All isolates were negative for congo red binding. Multi drug resistance observed among these isolates is of significance.